1990
DOI: 10.1128/mcb.10.7.3456
|View full text |Cite
|
Sign up to set email alerts
|

The serum-inducible mouse gene Krox-24 encodes a sequence-specific transcriptional activator.

Abstract: The mouse gene Krox-24 is transiently activated during cell cycle reentry. It encodes a protein with three zinc fingers similar to those of the transcription factor Sp1. Here we present a biochemical characterization of the gene products. Krox-24 mRNA is translated into two proteins of 82 and 88 kilodaltons, designated p82Krox-24 and p88Krox-24, respectively. p82Krox-24 is initiated at the first AUG codon of the open reading frame, whereas synthesis of p88Krox-24 starts at a non-AUG codon located upstream. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
130
1
2

Year Published

1991
1991
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(138 citation statements)
references
References 63 publications
(49 reference statements)
5
130
1
2
Order By: Relevance
“…Our data presented here indicate that a critical downstream e ector of bFGF function is the Egr-1 transcription factor. Activation of Egr-1 is suggested to be involved in the regulation of the G 0 /G 1 transition in mammalian cells (Lemaire et al, 1990). Besides bFGF, Egr-1 also targets many other growth factors and growth factor receptors such as PDGF-A, B (Khachigian et al, 1995(Khachigian et al, , 1996, tissue factor (Cui et al, 1996) and possibly epidermal growth factor receptor, suggesting that activation of Egr-1 may play a common role in the formation of a positive feedback autocrine loop, which is often involved in the mitogenic pathways and transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Our data presented here indicate that a critical downstream e ector of bFGF function is the Egr-1 transcription factor. Activation of Egr-1 is suggested to be involved in the regulation of the G 0 /G 1 transition in mammalian cells (Lemaire et al, 1990). Besides bFGF, Egr-1 also targets many other growth factors and growth factor receptors such as PDGF-A, B (Khachigian et al, 1995(Khachigian et al, , 1996, tissue factor (Cui et al, 1996) and possibly epidermal growth factor receptor, suggesting that activation of Egr-1 may play a common role in the formation of a positive feedback autocrine loop, which is often involved in the mitogenic pathways and transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, concomitant with the characteristic growth arrest, appearance of embryoid bodies, and outgrowth of neurites, RA-treated P19 cultures displayed upregulation of the transcription factor Egr-1. This was evident from an electrophoretic mobility shift assay using a GC-rich consensus DNA sequence, that binds to all members of the Egr family (Figure 6c) (Lemaire et al, 1990). Interestingly, induction of an Egr-like DNA binding activity preceded morphological alterations, but incubation with a relatively high concentration of NDF-b1 rapidly abolished the DNA binding activity of Egr-1.…”
Section: Erbb-3mentioning
confidence: 92%
“…This can be supported by the following points : (1) studies with dominant-negative MAPK have provided evidence that this pathway can lead to the stimulation of DNA synthesis [45], (2) Krox-24 induction is an early response event to all cell division signals examined so far [46][47][48][49], and (3) studies with anti-sense oligonucleotides have demonstrated that the induction of Krox-24 in lymphocytes is necessary for cell proliferation to occur [49,50]. This is presumably accomplished by the induction of a second wave of function-related genes that are controlled by Krox-24.…”
Section: Ntr Stimulation Induces Krox-24 Gene Expressionmentioning
confidence: 99%